Pengaruh Teori Rene Descartes terhadap Perubahan Pemikiran Teologi Teosentrisme Menuju Antroposentrisme - Revina Rahmadina; Radea Yuli A Hambali (Gunung Djati Conference Series, 2023)
This writing method uses literature study and literature review regarding the thoughts and history of related figures. The result of writing that Descartes' Rationalism thought made humans to use reason as a source of knowledge, humans must believe in something that they have seen, even everything that they see will not be completely true. This is reinforced by the thoughts of Hassan Hanafi who created a new theology that places humans at the center of everything so that he feels that his decisions provide justice for humanity. This writing discusses how theological theocentrism changes to anthropocentrism. The process of changing human thought that makes God the center of everything, towards humans being the center of everything. The changes that occur are considered to be due to criticism from the public who consider theology to be inhumane to humans. Theology is considered not to care about humans and requires humans to continue to submit and obey God. The author hopes that from this writing, people can find out about changes in thinking that have occurred, and how humans must live and control themselves. Humans have their own decisions and rights in making something the center of their lives.